Cakupan Imunisasi Dasar Lengkap Bayi pada Daerah Risiko Tinggi di Kabupaten Brebes Tahun 2019 - Deviana, Dika; Martini, Martini; Hestiningsih, Retno; Yuliawati, Sri; Sriatmi, Ayun; Jati, Sutopo Patria (Jurnal Ilmiah Mahasiswa, 2021)
In 2017 the number of complete basic immunization coverage in Indonesia had not yet reached the national standard coverage and for complete basic immunization coverage of infants in high-risk areas also tends to below. This study aimed to analyze the complete basic immunization coverage of infants in high-risk areas in Brebes Regency in 2019 by analyzing secondary data from research on infants' basic immunization coverage in high-risk areas of Brebes Regency. The research design used was cross-sectional. The population was mothers who have children aged < 2 years who lived in a high-risk area in Brebes Regency in 2019. The results were analyzed using a chi-square test. The study results showed that there were still many infants who did not get complete basic immunization, and the accuracy of basic immunization for infants was still low. Factors that affect the completeness of the complete basic immunization of infants are knowledge, perceptions, attitudes, and beliefs of the mother.